2017
DOI: 10.3390/app7010059
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Nanofiber Topography Directs the Tenogenic Differentiation of Mesenchymal Stem Cells

Abstract: Abstract:Tendon is commonly injured, heals slowly and poorly, and often suffers re-injury after healing. This is due to failure of tenocytes to effectively remodel tendon after injury to recapitulate normal architecture, resulting in poor mechanical properties. One strategy for improving the outcome is to use nanofiber scaffolds and mesenchymal stem cells (MSCs) to regenerate tendon. Various scaffold parameters are known to influence tenogenesis. We designed suspended and aligned nanofiber scaffolds with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…Our group and other groups have reported on tenogenic effect of substrate driven cytoskeletal alignment on MSCs previously 5, 1116, 21, 68, 69 . Collagen molecules are packed densely when they are registered in parallel (i.e.…”
Section: Discussionmentioning
confidence: 73%
“…Our group and other groups have reported on tenogenic effect of substrate driven cytoskeletal alignment on MSCs previously 5, 1116, 21, 68, 69 . Collagen molecules are packed densely when they are registered in parallel (i.e.…”
Section: Discussionmentioning
confidence: 73%
“…Overall, these results demonstrate that, by closely recapitulating the architecture of native tendon niches, the 3D topography of the Woven scaffold can promote similar organization of hTDCs and hASCs on the constructs, leading to highly elongated and aligned cell morphologies induced by contact guidance mechanisms, even after prolonged periods of in vitro maturation. Considering the increasing number of studies reporting on the tenogenic commitment of stem cells based on the cascade of cellular events triggered by the anisotropic fibrous alignment of scaffold substrates, it is reasonable to expect that the microstructure of the Woven scaffolds will likely guide seeded hTDCs and hASCs into a tenogenic‐like phenotype (either maintaining or differentiating, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…How biomaterial substrate mechanics and biochemistry interact to guide cell behavior has emerged as an important research topic with broad implications to biomaterial design [15][16][17]. Specifically for tendon repair, an aligned micro-or nanofiber structure is now understood to be a highly instructive biophysical cue that can direct tendon https://doi.org/10.1016/j.biomaterials.2020.120034 Received 30 March 2019; Received in revised form 4 April 2020; Accepted 5 April 2020 specific lineage differentiation [18][19][20][21][22][23][24][25]. Our own work has shown that deviations from aligned biomaterial surface structures may play a potentially important role in predisposing inflammatory response of attached tendon fibroblasts [26].…”
Section: Introductionmentioning
confidence: 99%